Application of liquid organic fertilizer from wild banana stem waste (Musa acuminate) and coconut husk as a culture medium for Spirulina platensis - Rubiyah, Rubiyah; Muliani, Muliani; Mahdaliana, Mahdaliana; Rusydi, Rachmawati; Mainisa, Mainisa (Universitas Malikussaleh, 2023)
Microalgae are single-celled microorganisms with pigments and can produce photosynthesis to produce food and oxygen. The addition of liquid organic fertilizer from wild banana stem waste (Musa acuminata) and coconut husk as a source of nutrients can be used to increase the cell density of Spirulina platensis. This research was conducted on September 18-27 at the Hatchery and Aquaculture Technology Laboratory, Aquaculture Study Program, Department of Fisheries and Marine, Faculty of Agriculture, Malikussaleh University. The method used in this study is an experimental method with a non-factorial Complete Randomized Design (RAL) of 5 treatments and 3 repeats. The study is treatment A Control (Walne fertilizer), treatment B (Mixture of POC Waste of forest banana stems and coconut husk 12 ml / L of sea water), treatment C (Mixture of POC Waste of forest banana stems and coconut husk 14 ml / L of seawater), treatment D (Mixture of POC Waste of forest banana stems and coconut husk 16 ml / L of seawater), treatment E (Mixture of POC Forest banana stem waste and coconut husk 18 ml/L seawater). The results of this study showed that the use of POC from forest banana stem waste and coconut husk as a culture medium for Spirulina platensis had a real effect with F calculate 43,850 > F tabel (0.05) 3.48 to the peak population and had a real effect on the growth rate of Spirulina platensis with F calculate (26,884) > F table (0.05) 3.48.Keywords: Coconut husk; POC; Spirulina platensis; Wild banana stem waste.